MODERN TENDENCIES OF CLIMATE, WATER RESOURCES AND ECOSYSTEMS CHANGES IN THE MIDDLE-LOWER PART OF SOUTHERN BUG RIVER, UKRAINE - Boychenko, Svitlana; Movchan, Yaroslav; Tyshchenko, Oksana (Proceedings of National Aviation University (archive), 2017)
Purpose: Analyze the features of climate and water regime change in the northwestern part of the Southern Bug River basin in second half of the 20th century and at the beginning of the XXI century in the region of the South-Ukrainian Nuclear Power Plant (SUNPP). Assess the impact of the SUNPP on the microclimatic conditions and identify possible threats to the biotic diversity of natural ecosystems which are associated with environmental changes. Methods: The main results of work are obtained on the basis of empirical materials by statistical analysis and analytical review of published materials. Results: The energy production at the SUNPP requires significant amount of water from Southern Bug River for cooling. Due to the climatic changes, namely, with the increase of the average annual air temperature and the decrease the amount of precipitation (in the upper and middle part of the river), the operations of the connected with cooling became complicated. Discussion: The SUNPP activity in the modern limits already have a negative impact on the environment, but the concern of ecologists is exacerbated by the possible increase of the Oleksandrivske reservoir to a mark of +20 m, which will increase the load on natural ecosystems and the society, and will violate the number of international and national legal acts, while not taking into account current trends of climate change.